2013
DOI: 10.1080/09585192.2012.725079
|View full text |Cite
|
Sign up to set email alerts
|

Key factors influencing Korean expatriates' and spouses' perceptions of expatriation and repatriation

Abstract: Lack of satisfaction with repatriation has been identified as one of the major causes for high turnover of employees returning from international assignments. Extant literature emphasises the importance of organisational training and mentoring, career advancement, and family and spouse support throughout expatriation and repatriation. In the current study we explored factors influencing Korean employees' and spouses' perceptions of expatriation and repatriation. The study involved semi-structured, in-depth int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
47
2
5

Year Published

2016
2016
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(58 citation statements)
references
References 68 publications
4
47
2
5
Order By: Relevance
“…Other studies have revealed that repatriates often develop a negative attitude toward their organization when they perceive a lack of support upon their return (Nery-Kjerfve & McLean, 2012), which consequently influences job satisfaction (Cho et al, 2012). The high turnover rates amongst repatriates in some studies Yan et al, 2002) supports these ideas in so far as they have been explained as indicators of the failure of organizations to effectively manage employees' expectations, leading to perceptions that the organization has failed to fulfill its implicit promises.…”
Section: Research On Repatriate's Psychological Contractmentioning
confidence: 64%
“…Other studies have revealed that repatriates often develop a negative attitude toward their organization when they perceive a lack of support upon their return (Nery-Kjerfve & McLean, 2012), which consequently influences job satisfaction (Cho et al, 2012). The high turnover rates amongst repatriates in some studies Yan et al, 2002) supports these ideas in so far as they have been explained as indicators of the failure of organizations to effectively manage employees' expectations, leading to perceptions that the organization has failed to fulfill its implicit promises.…”
Section: Research On Repatriate's Psychological Contractmentioning
confidence: 64%
“…Lee and Kartika (2014) found that social capital could enhance the success of expatriate adjustment which could further influence expatriate performance. Past research had shown that social interaction and relationships during global assignments were one of the critical predictors of cultural adjustment (Lee, 2005;Aycan, 1997;Caligiuri & Lazarova, 2002). The involvement of expatriates in social activities in the host country rather than only work related activities enhanced their abilities to adjust effectively (Liu & Lee, 2008).…”
Section: Mediating Role Of Cultural Adjustmentmentioning
confidence: 99%
“…Ishimaru (2013) indicated that employees would enhance the trust in the organization as well as change their attitudes and behaviors when presenting a positive perception of organizational policies, programs and practice. Cho et al (2013) mentioned that the more active attitude of an organization promoting learning, the employees, under the long-term, would devote to the organization to result in a thick learning climate in the organization, which would be slowly be stabilized in employees' minds and be considered as the essential condition for being the organizational member, to further enhance the perception of the organization and present beneficial behaviors to the organization. Accordingly, the following hypothesis is proposed in this study:…”
Section: H1mentioning
confidence: 99%
“…Referring to Cho, Hutchings, and Marchant (2013), the sources of organizational learning in this study contain information gathering, information transmission, and information sharing and analysis.…”
Section: Organizational Learningmentioning
confidence: 99%
See 1 more Smart Citation